RELASI MAYORITAS-MINORITAS DAN RADIKALISME DALAM KONSTRUKSI MEDIA ISLAM - Rusmulyadi; Lida (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2017)
This research analyzes the issue of majority-minority relations and radicalism which arised in the media during 2015. The Construction of discourse to be traced based on incident of Tolikara and Aceh Singkil to the issue of majority-minority relations and the policy of blocking Islamic media online that promoted radicalism the issue of religious radicalism. Starting from this framework, the formulation of the research to be answered is how the construction built by Islamic media online in Indonesia in the current issues of religious during 2015.As the analysis method of this study would used the analysis of discourse based on the framework of social semiotics M.A.K Halliday. Halliday has developed a framework that makes it possible to analyzed the interaction between text and context that is based on three concepts: field of discourse, tenor of discourse and mode of discourse. The results indicated that the framework of Islamic media online discourses more positioning itself as media involved in formulating the majority-minority relations. The Islamic media can not be independent when constructing incident of Tolikara and Aceh Singkil were dragging the issue of majority-minority relations.The discourse building of islamic media about radicalism in Indonesia with reflection on blocking Islamic media online focuses more on policy the handling of his radicalism rather than looking into content of Islamic media.